An Incidental Finding of Appendiceal Gastrointestinal Stromal Tumor with Abundant Skeinoid Fibers: A Rare Case Report with Insights from a Comprehensive Literature Review - Yu Liu; Yaomin Chen; Asra Feroze; Zhiyan Fu (Diagnostics)
Background and Clinical Significance: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract but are exceedingly rare in the appendix, with only 20 cases reported in the literature. Due to their rarity, clinical behavior, histopathologic features, and management of appendiceal GISTs remain poorly understood. Case Presentation: We present the case of a 74-year-old man who underwent a right hemicolectomy for colonic adenocarcinoma, during which an incidental 1.2 cm appendiceal GIST was discovered. Histopathological examination revealed spindle cell morphology with abundant skeinoid fibers (SF), minimal mitotic activity (<1/50 HPF), and no nuclear atypia. Immunohistochemical staining confirmed positivity for CD117, DOG1, and CD34. The tumor was classified as low risk based on its size and mitotic count, and the patient remained recurrence-free at a 4-month follow-up. Conclusions: Our case expands the limited literature on appendiceal GISTs by demonstrating their histopathological and immunohistochemical features, favorable prognostic outcomes, and potential for incidental detection during surgeries for unrelated conditions. However, additional studies are needed to further elucidate their molecular characteristics and overall clinical behavior.